2021
DOI: 10.1038/s41598-020-79971-y
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of iron deficiency anemia on pregnancy outcome and offspring development and intervention of three iron supplements

Abstract: Iron deficiency anemia (IDA) is a common micronutrient deficiency among pregnant women with severe consequences including impaired immuno-inflammatory system, premature birth, fetal death etc. The present study aimed to investigate the effects of three iron supplements on IDA female rats and their offspring. The IDA female rat model was established with low iron diet and the rats were then mated. After pregnancy, rats were fed diets containing different iron supplements (iron polysaccharide complex, iron prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 23 publications
3
26
0
3
Order By: Relevance
“…Approximately 20 million infants are born with LBW worldwide each year [9]. The notion that maternal anemia during pregnancy relates to LBW has received strong evidential support across epidemiological, medical, and animal studies [10][11][12][13]. A recent systemic meta-analysis found that anemia (hemoglobin (Hb) concentration ≤ 110 g/L) overall or at any time during pregnancy increased the risk of LBW with an adjusted odds ratio: 1.23 (95% CI: 1.06, 1.43) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 20 million infants are born with LBW worldwide each year [9]. The notion that maternal anemia during pregnancy relates to LBW has received strong evidential support across epidemiological, medical, and animal studies [10][11][12][13]. A recent systemic meta-analysis found that anemia (hemoglobin (Hb) concentration ≤ 110 g/L) overall or at any time during pregnancy increased the risk of LBW with an adjusted odds ratio: 1.23 (95% CI: 1.06, 1.43) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy with IDA can cause serious short-term and long-term complications for mothers, fetuses, and newborns. [21][22][23][24] After iron supplementation, the HGB, MCV, and all iron metabolism parameters were significantly improved in the b + IDA and IDA groups, suggesting that iron supplementation was effective in both groups. Moretti et al 25 demonstrated that multiple doses a day are not optimal for iron supplementation.…”
Section: Discussionmentioning
confidence: 92%
“…FTH1 is known to be elevated in response to high iron levels as a cellular iron storage protein and major regulator of the cellular labile iron pool [60]. Iron supplementation in both iron-deficient anemia mice and their offspring significantly upregulated FTL levels with improved physical growth compared to untreated mice [61]. We have seen low FTH1 and increased iron accumulation, with adipocyte size reduced by 45.5%, adipose tissue TG decreased by 60%, and serum TG decreased by 56.6%; however, the interaction between them is yet to be studied.…”
Section: Discussionmentioning
confidence: 99%